Comparative effectiveness of antiarrhythmic drugs on cardiovascular hospitalization and mortality in atrial fibrillation. (May 2013) - Lakdawalla, Darius; Turakhia, Mintu P; Jhaveri, Mehul; Mozaffari, Essy; Davis, Pamela; Bradley, Lily; Solomon, Matthew D
Aim: To assess, through a systematic review, evidence for the effects of antiarrhythmic drugs (AADs) on cardiovascular (CV) hospitalization and mortality.Materials & methods: English language articles were identified using MEDLINE, EMBASE and the Cochrane Clinical Trial Registry and were screened for study applicability and methodological quality.Results: Out of 3526 identified studies, 38 were selected for analysis (19 evaluated individual AADs, 13 compared rate- versus rhythm-control strategies, and 6 evaluated multiple AADs but did not report outcomes for individual agents). None of the studies examining individual AADs employed the CV hospitalization end point used in ATHENA (the reference trial). There were no head-to-head comparisons of individual AADs on CV hospitalization. Most high-quality studies used multidrug rate- versus rhythm-control strategies.Conclusion: Assessment of the comparative effectiveness of individual AADs on CV hospitalization and mortality end points is not possible with the current evidence.